Winds of Change in Nursing Education - Marietta Stanton (Rural Nurse Organization; Binghamton University, 2005)
I wanted to highlight changes that are occurring in nursing especially with regard to nursing education. One initiative which is gathering much support and adoption is a role proposed by the American Association of Colleges of Nursing (AACN). It is called the Clinical Nurse Leader (CNL). According to AACN, the role has been created in response to the Institute of Medicine's landmark report, To Err is Human: Building a Safer Health System, which called on health care systems to reorient their efforts to reduce medical errors and improve patient safety. In addition AACN perceived that in nursing we have not succeeded in differentiating practice of RNs with different educational preparation. Numerous reports have shown that care provided to patient is not high quality. In addition AACN believes that the knowledge base for nurses has increased dramatically. Based on these three complex issues this new role was created. AACN appointed a task force to examine new educational models that would develop a "New Nurse" graduate, educated beyond a four year baccalaureate program with a new license and a new license and scope of practice.